Effect of temperature, pH and NaCl on nisin activity against Lactobacillus fructivorans - Herman, Cristian (2009)
The aim of this work was to determine the influence of pH, sodium chloride concentration and the combination of different temperatures and periods of exposure on the antimicrobial activity against Lactobacillus fructivorans. Turbidity of the different system conditions was monitored in order to establish the microorganism growth. The effect of temperatures ranging from 60 to 120ºC during periods of 10 to 60 minutes was evaluated. Nisin activity was only changed by temperatures ranging from 100 to 120ºC, in several exposure times. A pH range between 3.5 and 7 was tested. The highest inhibitory effect was recorded for neutral pH and lightly acidic conditions. Sodium chloride concentrations studied were 1 and 2 % w/v. The latter value helped to enhance the inhibitory effect of the bacteriocin. These results show the influence that the studied factors exert on nisin activity against L. fructivorans and suggest that they have to be taken into account when nisin is to be used as a biopreservative in food.